Standard form : f(x) = ax^2 +bx+c

x^2 + 8x + 12 = 0 (x+2)(x+6)=0; solve for x , x= -2,-6first convert the standard form into vertex form

x^2 + 8x + 12 = 0

(x+2)(x+6)=0;

solve for x , x= -2,-6

first convert the standard form into vertex form

Vertex form : f(x)= a(x-h)^2+k

h = -b/2a

k = f(h)

h = -8 / (2*1) = -4 k = f(-4) = (-4)^2 + 8*(-4) + 12 = = 16 -32+12 = -4f(x) = (x-(-4))^2 -4f(x) = (x+4)^2 -4

h = -8 / (2*1) = -4

k = f(-4) = (-4)^2 + 8*(-4) + 12 =

= 16 -32+12 = -4

f(x) = (x-(-4))^2 -4

f(x) = (x+4)^2 -4

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up